KARAKTERISTIK FAKTOR-FAKTOR RISIKO TERJADINYA NEUROPATI DIABETIK PERIFER PADA PASIEN DIABETES MELLITUS - Ahmad Mahdi Rezkiansyah (2023)
Background: Diabetes Mellitus (DM) is a metabolic disease with chronic complications, peripheral diabetic neuropathy (DPN) being one of them. Multiple risk factors, including age, duration of diabetes, smoking status, body mass index (BMI), HbA1c variability, of which Mean HbA1c (M-HbA1c) is one, hypertensive status, triglyceride levels, total cholesterol levels, low-density lipoprotein (LDL) levels, and high-density lipoprotein (HDL) levels, contribute to peripheral diabetic neuropathy. This study will identify the factors that affect DPN output. Methods: A retrospective, cross-sectional study of DM patients with peripheral diabetic neuropathy complications and those who do not at PON Jakarta Hospital between January 2021 and December 2022. Using age, BMI, M-Hba1c variability, hypertension status, triglycerides, total cholesterol, LDL, and HDL, a comparison is made between the DPN and control groups. Chi-square analysis and logistic regression were used to determine the factors that influence DPN. Results: There were 62 patients diagnosed with DPN and 51 patients without DPN. Chi-square analysis revealed a correlation between the variability of M-HbA1c (p = 0.003), triglycerides (p = 0.002), total cholesterol (p = 0.001), and LDL (p = 0.016) and the incidence of DPN in patients. Variability of M-HbA1c (p = 0.032, OR: 0.340, 95% CI), triglyceride levels (p = 0.008, OR: 0.430, 95% CI), and HDL levels (p = 0.024, OR: 0.325, 95% CI) was revealed by logistic regression analysis. Conclusion: DPN correlates with a high degree of variability in M-HbA1c, triglyceride levels, total cholesterol, and LDL. Consequently, diabetics must constantly monitor their respective health conditions in order to prevent diabetesrelated complications.